2014
DOI: 10.1111/pan.12381
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter, randomized, double‐blind placebo‐controlled, single dose trial of the safety and efficacy of intravenous ibuprofen for treatment of pain in pediatric patients undergoing tonsillectomy

Abstract: Summary Background Tonsillectomy is one of the most common pediatric procedures in the United States. An optimal perioperative pain control regimen remains a challenge. Intravenous ibuprofen administered at induction of anesthesia may be a safe and efficacious option for postoperative tonsillectomy pain. Objectives To determine whether preoperative administration of intravenous ibuprofen (IV‐ibuprofen) can significantly decrease the number of doses of postoperative fentanyl when compared with placebo in pediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 13 publications
3
62
0
4
Order By: Relevance
“…Although previous studies have reported adequate analgesia with lower intraoperative doses of morphine, with the use of shorter-acting analgesics such as fentanyl in combination with nonopioid analgesics, the longer-acting agent morphine, when administered in appropriate doses with appropriate postoperative monitoring, offers the benefit of providing analgesia beyond the immediate recovery time in the PACU. 20,22,23 In these subjects, the average time to the first request for an additional analgesic agent was 4 to 5 hours after admission to the inpatient ward. Although decreasing the morphine dose could highlight an opioid-sparing effect of the intravenous acetaminophen in the immediate PACU period, it may also lead to rebound postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have reported adequate analgesia with lower intraoperative doses of morphine, with the use of shorter-acting analgesics such as fentanyl in combination with nonopioid analgesics, the longer-acting agent morphine, when administered in appropriate doses with appropriate postoperative monitoring, offers the benefit of providing analgesia beyond the immediate recovery time in the PACU. 20,22,23 In these subjects, the average time to the first request for an additional analgesic agent was 4 to 5 hours after admission to the inpatient ward. Although decreasing the morphine dose could highlight an opioid-sparing effect of the intravenous acetaminophen in the immediate PACU period, it may also lead to rebound postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…Такие препараты обладают не только мощным противовоспалительным действием, но и обеспечивают упреждающую анальгезию, если применяются до разреза. НПВС противопоказаны у пациентов с бронхиальной астмой, поливален-тными аллергиями, гастропатиями [13].…”
Section: иннервацияunclassified
“…Применение упреждающей (преэмптивной) анальгезии (введение НПВС: у детей старшего возраста -кетопрофен в дозе 2 мг/кг, у детей младшего возраста -парацетамол в дозе 15 мг/ кг) и инфильтрационной анестезии позволяет снизить опиоидную нагрузку в периоперацион-ный период [18]. Согласно современным дан-ным, однократное внутривенное введение НПВС в стандартной дозировке при ЛОР-операциях характеризуется безопасным профилем и не при-водит к увеличению времени кровотечения [13]. По данным ряда исследований, внутривенное введение 1 дозы НПВС или парацетамола сни-жает опиоидную нагрузку в ранний послеопера-ционный период, а также частоту возникновения послеоперационных тошноты/рвоты и после-операционного делирия [17,19,20].…”
Section: иннервацияunclassified
“…Entre las 0-48 horas y 24-48 horas post alta hospitalaria, el grupo de pacientes tratados con ibuprofeno i.v. presentó significativamente menor emesis que el grupo control (23).…”
Section: Dolorunclassified